Upper arm basilic vein elevation as a solution for forearm ulnar-basilic arteriovenous fistulae with cannulation problems. Issue 3 (May 2019) - Mallios, Alexandros; Jennings, William; Costanzo, Alessandro; Boura, Benoit; Combes, Myriam
Background: Ulnar-basilic arteriovenous fistula is an alternative option when a radiocephalic arteriovenous fistula is not feasible. We review our technique of basilic vein transposition in the upper arm for difficult to puncture forearm ulnar-basilic non-transposed arteriovenous fistulae. Technical note: Three patients were referred for forearm ulnar-basilic arteriovenous fistulae with difficult cannulation where the forearm basilic vein was left in situ (non-transposed). Surgeon performed ultrasound examination confirmed a patent arteriovenous fistula with adequate diameter and flow, draining to the basilic vein in the forearm and into the upper arm. Recurrent new and resolving hematomas were present surrounding the forearm basilic vein resulting from difficult cannulation issues and problems maintaining needle position due the posterior-medial ulnar-basilic arteriovenous fistula position and mobility of the non-transposed forearm basilic vein. A basilic vein transposition elevation procedure was performed in the upper arm starting at the level of the elbow to a few centimeters below the axilla. Branches of the dilated basilic vein were ligated, the median cutaneous nerve was preserved, and the vein was elevated from its native position to a superficial and anterior location. Although difficult, dialysis access had been continued in the forearm during a brief period and none required catheter placement. Reliable dialysis access was successfully initiated using the newly transposed basilic vein in the upper arm 3–4 weeks after the procedure, maintaining arterial inflow based on the original ulnar-basilic arteriovenous fistula anastomosis at the wrist. None of the patients required further interventions with follow-up of 8, 15, and 22 months.